Practicing education of the mineral processing engineering discipline in Henan Polytechnic University. Issue 1 (1st January 2019) - Cheng, G.; Zhang, C.X.; Fan, Y.C.; Li, F.F.; Lin, L.; Zhu, X.B.
ABSTRACT: A plan for national education to train outstanding engineers has been put into practice at Henan Polytechnic University (HPU). Practical education is a basic characteristic of engineering education. This paper proposed ideas and models to reform the mineral processing engineering education system and also described the discipline and the objective of cultivating students for careers in mineral processing engineering. On the basis of a survey and analysis of the quality of graduate student cultivation, we established a practical teaching system of 'four levels, seven categories' and the effect of this system was initially apparent.